Coupling CFD with detailed microkinetic modeling in heterogeneous catalysis - Maestri, Matteo; Cuoci, Alberto (Chemical engineering science, 2013)
The atomic-scale understanding of a catalytic process is crucial for the rational development of catalytic technologies. It requires the identification of the dominant reaction mechanism, that is an intrinsic multiscale property of the system. In this respect, it is of utmost importance to obtain a fundamental understanding about the interactions of the catalyst reactivity with the surrounding flow field in the reactor. Here, we propose a new solver (catalyticFOAM), that allows for the solution of Navier–Stokes equations for complex and general geometries for reacting flows at surfaces, based on a detailed microkinetic description of the surface reactivity. The catalyticFOAM solver exploits the operator-splitting technique, based on the separation of transport and reaction terms. The proposed numerical algorithm makes possible the simulation of multidimensional systems with complex and detailed kinetic mechanisms, overcoming the unfeasible computational effort that would be required by fully-coupled algorithms. Examples concerning the H2 fuel rich combustion on Rh are presented as showcases in structured and randomly packed reactors. The proposed approach represents an essential step for the first-principles based multiscale analysis of catalytic processes and paves the way toward the rational understanding and development of new reaction/reactor concepts. •We apply the operator-splitting-technique to the CFD of reacting flows at surfaces.•The algorithm makes possible the simulation of very general catalytic reactors.•The approach allows for the fundamental multiscale analysis of catalytic processes.•Simulations of complex geometries with microkinetic models are presented.